Marketplace Penjualan Produk UMKM Kabupaten Bireuen Sebagai Portal Community Marketing Berbasis Web - T Irfan Fajri, Mutasar, Intan Tursina (LPPM-UNIKI, 2023)
The advancement of online marketing has opened up extensive opportunities for Small and Medium Enterprises (SMEs) to expand their reach to international markets. This research aims to create a comprehensive sales information system for showcasing and selling unique handicraft products through a web portal, administered by designated personnel. This system will not only facilitate the marketing of fashion items but also emphasize the promotion of handmade crafts.